Ultra wideband impulse radio wireless system - Dinh, Hung Tu (2013)
This project proposes and evaluates an ultra low power medium access control (MAC) protocol specifically devoted for wireless sensor networking application using ultra wideband impulse radio (UWB-IR) technology. The targeted applications are expected to be implemented in an ad hoc fashion, with individual nodes remaining largely inactive for extended period of time unless they detect some triggering data to be transmitted. Distinct characteristics of UWB-IR sensor networks from the traditional wireless networks are discussed to evaluate the proposed protocol. Energy efficiency in the proposed protocol is justified against the common sources of energy loss such as collision, overhearing, control overhead, and idle listening. Finally, MATLAB object-oriented programming is deployed to demonstrate the performance.